2023
DOI: 10.3390/antiox12020389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2-Nitroimidazoles in the Response of FaDu Cells to Ionizing Radiation and Hypoxia/Reoxygenation Stress

Abstract: Cellular adaptations to hypoxia promote resistance to ionizing radiation (IR). This presents a challenge for treatment of head and neck cancer (HNC) that relies heavily on radiotherapy. Standard radiosensitizers often fail to reach diffusion-restricted hypoxic cells, whereas nitroimidazoles (NIs) [such as iodoazomycin arabinofuranoside (IAZA) and fluoroazomycin arabinofuranoside (FAZA)] can preferentially accumulate in hypoxic tumours. Here, we explored if the hypoxia-selective uptake of IAZA and FAZA could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Worth mentioning here is that Rashed et al have previously reported a higher SER value for IAZA in FaDu cells under hypoxia. 27,28 The discrepancy can be explained by the shorter incubation used in this study (3 h vs 24 h). Additional in vivo studies are required to corroborate the radiosensitization effects seen with nanoIAZA in vitro and to extend the potential use of this drug-delivery system as a hypoxic radiosensitizer.…”
Section: ■ Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Worth mentioning here is that Rashed et al have previously reported a higher SER value for IAZA in FaDu cells under hypoxia. 27,28 The discrepancy can be explained by the shorter incubation used in this study (3 h vs 24 h). Additional in vivo studies are required to corroborate the radiosensitization effects seen with nanoIAZA in vitro and to extend the potential use of this drug-delivery system as a hypoxic radiosensitizer.…”
Section: ■ Introductionmentioning
confidence: 77%
“…A hypoxic tumor model based on FaDu tumor cellsan established human hypopharyngeal squamous cell carcinomawas used according to the study reported by Vaupel et al In a previous study, it was concluded that the oxygenation status of FaDu tumors is heterogeneous and independent of the tumor volume . Chemotoxicity evaluation of IAZA and nano IAZA was assessed in male NU/NU mice bearing FaDu tumors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations